Summertime, and the Library Is Easy… - Norman, Steve (Maine Policy Review, 2013)
Libraries in Maine are busy places during the summer. Unlike libraries in some other parts of the country where hours of operation get pared back for the summer, most libraries in Maine are much busier than in the rest of the year, largely due to the influx of summer visitors.